Nurses’ knowledge of the provision of oral care for patients with dysphagia - Durgude, Y.; Cocks, Naomi (Mark Allen Healthcare, 2011)
There has been little research on the provision and adaptation of oral care for patients with dysphagia in nursing homes. This study collected data via a questionnaire specifically on the knowledge of oral hygiene and the current oral care practices for patients with dysphagia. Fifty-three registered nurses (RNs) completed the questionnaires. The results of the questionnaire indicated that although RNs gave more oral care daily to their patients with dysphagia than to their patients without dysphagia, they had limited knowledge of drugs that affect oral care and of medical conditions associated with poor oral hygiene. Of particular concern was the limited knowledge of the link between dysphagia, oral hygiene and pneumonia and that some of the current oral care practices may be putting patients who have dysphagia at increased risk of developing pneumonia. These results are discussed in light of previous research on the topic and recommendations are made with regards to oral care training.